Humidity-Responsive Photonic Films and Coatings Based on Tuned Cellulose Nanocrystals/Glycerol/Polyethylene Glycol - Amin Babaei-Ghazvini (MDPI AG, 2021)
It has been extensively reported that cellulose nanocrystals (CNCs) can represent structural colors due to their unique chiral-nematic self-assembly. However, the application of this remarkable structure does need further investigation. It has been challenging to keep the selective reflection band (SRB) resulting from the CNC structure in the visible spectrum. Herein, composition of CNC colloidal suspensions with polyethylene glycol (PEG) and glycerol (Gly) have been studied to develop humidity-responsive sensors in the form of coatings and films. The fabricated samples were characterized for their mechanical properties, optical properties, water uptake capacity, water contact angle, and surface roughness. Additionally, the chemical structure of the samples was studied with FTIR spectroscopy. The produced humidity indicators on microbial glass slides were maintained and tested in a different relative humidity range from 20% to 98% with a different color response from blue to red, respectively. The color change of the humidity sensors was reversible for several cycles. It should be noted that the color change can be detected easily by the naked eye. The water uptake test showed that pure CNC and CNC/Gly had the lowest (34%) and highest (83%) water absorption levels. The mechanical tests for CNC/PEG composites showed the highest tensile strength (40.22 MPa). Moreover, microstructural characterizations confirmed the CNC pitch formation in all the samples. Addition of the fillers increased the CNC pitch, resulting in a mesoporous film formation. These produced humidity sensors are promising candidates in food and drug packaging due to their biodegradability, biocompatibility, and cost-effectiveness.